Delivery of community-based antiretroviral therapy to maintain viral suppression and retention in care in South Africa - Wang, M; Violette, LR; Dorward, J; Ngobese, H; Sookrajh, Y; Bulo, E; Quame-Amaglo, J; Thomas, KK; Garrett, N; Drain, PK (Lippincott, Williams & Wilkins, 2023)
Background: To determine whether the Centralized Chronic Medication Dispensing and Distribution (CCMDD) program in South Africa's differentiated ART delivery model affects clinical outcomes, we assessed viral load (VL) suppression and retention in care between patients participating in the program and those receiving the clinic-based standard of care.